Desain Didaktis Pada Pembelajaran Jarak Dalam Ruang Dimensi Tiga Berbantuan Geogebra Untuk Siswa Kelas X SMA - Nadila, Ririn Ikhsi; Fuadiah, Nyiayu Fahriza; Isroqmi, Asnurul (PPSDP Undergraduate Journal of Educational Sciences, 2025)
This research is Didactical Design Research (DDR) research which aims to design didactical designs on the concept of distance in three-dimensional space. Didactical design is designed by taking into account students’ Learning Obstacles and Learning Trajectories. This research has three stages which include the prospective analysis stage, meta pedadidactic analysis stage and retrospective analysis stage. The results of this research indicate that students experience learning obstacles in the concept of distance in three-dimensional space, namely students experience difficulty in understanding the prerequisite material as a basis for studying distance concept material in three-dimensional space. The Hypothetical Learning Trajectory (HLT) in this research was prepared based on the Learning Obstacle experienced by students. Didactical design is in accordance with the Hypothetical Learning Trajectory (HLT), namely carrying out Adaptation, Action, Formulation and Validation to determine the perfect design by paying attention to the Learning Obstacles experienced by students from understanding prerequisite material about vectors to understanding distance in three-dimensional space using the application geogebra to get maximum results with a significant reduction impact on final identification.